2019
DOI: 10.1038/s41419-019-2034-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hexosamine metabolism drives metabolic and signaling networks involving hyaluronan production and O-GlcNAcylation to exacerbate breast cancer

Abstract: The hexosamine biosynthetic pathway (HBP) metabolically regulates dynamic cellular events by linking nutrient availability to numerous signaling networks. Significant alterations in the HBP are often associated with cancer pathogenesis. In this study, we investigated the molecular events underlying cancer pathogenesis associated with enhanced HBP flux. Multidimensional analysis of microarray datasets demonstrated up-regulation of genes encoding HBP enzymes in clinical breast cancers and revealed that co-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Large quantities of HA in ECM stimulate interactions with CD44 to cause chemoresistance in patients with head and neck cancer patients [ 244 ]. HA activates growth signals, such as the PI3K/Akt pathway, thus leading to chemotherapy resistance in breast cancer [ 245 ]. By activation of TGFβ/Smad2 signals and ECM, HA-HMMR conferred resistance to chemotherapy in gastric cancer [ 246 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Large quantities of HA in ECM stimulate interactions with CD44 to cause chemoresistance in patients with head and neck cancer patients [ 244 ]. HA activates growth signals, such as the PI3K/Akt pathway, thus leading to chemotherapy resistance in breast cancer [ 245 ]. By activation of TGFβ/Smad2 signals and ECM, HA-HMMR conferred resistance to chemotherapy in gastric cancer [ 246 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…New inhibitors for GFAT are also in development (30)(31)(32). Another advantage of targeting GFAT/HBP is that inhibition of the pathway itself has anti-cancer properties, as we (13)and others have demonstrated (33)(34)(35)(36). HBP is frequently hyperactive in cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Multidimensional analysis of microarray datasets demonstrated that HBP enzymes are up-regulated in breast cancer and that the co-expression of HAS2 and the HBP rate limiting enzyme glutamine-fructose-6-phosphate transaminase (GFAT) is associated to a poor prognosis in advanced cancer patients. 73 Moreover, the enhancement of HBP flux is related to the activation of pro-tumorigenic pathways and elevated overall levels of O-GlcNAcylation. 73 The over-production of HA correlates to plasticity of breast cancer cells, where the acceleration of the metabolism of hexosamine, along with a metabolic shift toward glycolysis, reverts cancer cells phenotype to stem cell states.…”
Section: Influence Of Udp-sugars Availability On Ha Synthesismentioning
confidence: 99%
“…73 Moreover, the enhancement of HBP flux is related to the activation of pro-tumorigenic pathways and elevated overall levels of O-GlcNAcylation. 73 The over-production of HA correlates to plasticity of breast cancer cells, where the acceleration of the metabolism of hexosamine, along with a metabolic shift toward glycolysis, reverts cancer cells phenotype to stem cell states. 74 The analysis of human breast cancer biopsies showed a dramatic increment of UDP-GlcNAc and UDP-GlcUA in the tumors, elevated GFAT levels and a strong accumulation of HA as compared to normal glandular tissue obtained from breast reductions.…”
Section: Influence Of Udp-sugars Availability On Ha Synthesismentioning
confidence: 99%